TYPES OF MEDIA TEXT LANGUAGE - Maxmudova, Fotima (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The language used in media texts plays a crucial role in shaping the way fact that is presented and received by audiences. This article explores the different types of language used in various media texts, including newspapers, television. By examining the characteristics and impact of different styles of language, we can gain a better understanding of how media texts influence public perception and engagement.